Analisis Kebutuhan Pengembangan Media Mind Mapping untuk Meningkatkan Keterampilan Berpikir Kausalitas pada pembelajaran Sejarah di SMA - Putri, Dhea Aningrum; Afriani, Rini (Jurusan Sejarah FIS UNP, 2026)
ABSTRACT This research is motivated by the low causal thinking skills of students in understanding the History learning material delivered by teachers, especially in the material on the Japanese Occupation of Indonesia in the Merdeka Curriculum. This study aims to analyze the need for Mind Mapping media development to improve causality skills in History learning in high school. The method used is a mixed method involving 30 grade XI students and a history teacher at SMA Negeri 2 Kota Sungai Penuh. Data were collected through observation, interviews and questionnaires via Google Form, then analyzed quantitatively and qualitatively. The results of the study indicate that the level of causal thinking of students in History learning is still low, characterized by difficulty analyzing the cause and effect of a Historical event. Teachers and students stated the need for learning media that can help visualize history learning materials more systematically and interestingly. Based on the results of the needs analysis, mind mapping media is considered to have the potential to be developed as a learning medium that can help students organize information, understand cause and effect relationships, and improve causal thinking skills, especially in History learning.